Legitimasi Kekuasaan Ādityawarman di Kerajaan Malayu Berdasarkan Sumber-Sumber Prasasti: Legitimasi Kekuasaan Ādityawarman di Kerajaan Malayu Berdasarkan Sumber-Sumber Prasasti - Pratiwi, Eka; Hafiful Hadi Sunliensyar; Ari Mukti Wardoyo Adi (BRIN, 2024)
The Malayu Kingdom was one of the Hindu-Buddhist kingdoms on the island of Sumatra. The kingdom achieved its glory during the reign of King Ādityawarman (1347-1374 AD). One of the archaeological remains from this period are inscriptions that describe life in the Malayu Kingdom. The problems to be researched in this study are the elements of legitimacy contained in the text of Ādityawarman’s inscriptions and the form of legitimacy of Ādityawarman’s sovereignty in the Malayu Koingdom. The results of observations of 13 inscriptions from the Ādityawarman’s period, obtained 6 inscriptions that contain elements of legitimacy of sovereignty, namely Pagaruyung I Inscription, Pagaruyung II Inscription, Saruaso I Inscription, Kuburajo I Inscription, Amoghapāśa Inscription, and Ombilin Inscription. The method used to answer research problems is the epigraphic reserach method, consisting of data collection, data processing (analysis), interpretation (problem interpretation), concluding, and presenting research results. The results showed that there are 2 forms of legitimization of the Hindu-Buddhist period in the archipelago, namely equalization of supernatural entities (gods) and nāmābhiṣeka. The equalized gods consist of Lord Indra, Adibuddha, and Avalokitesvara. In addition, there are also other forms of legitimacy in the Ādityawarman inscription through several symbols, namely kala head ornaments, vajra ornaments, and Bhairawa statues. Based on Max Weber’s classification of legitimacy, the form of legitimacy practiced by King Ādityawarman in the Malayu Kingdom is classified as charismatic legitimacy.